(2m+7)/6=(5m-2)/5

Simple and best practice solution for (2m+7)/6=(5m-2)/5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (2m+7)/6=(5m-2)/5 equation:



(2m+7)/6=(5m-2)/5
We move all terms to the left:
(2m+7)/6-((5m-2)/5)=0
We calculate fractions
2m/()+(-((5m-2)*6)/()=0
We calculate terms in parentheses: +(-((5m-2)*6)/(), so:
-((5m-2)*6)/(
We multiply all the terms by the denominator
-((5m-2)*6)
We calculate terms in parentheses: -((5m-2)*6), so:
(5m-2)*6
We multiply parentheses
30m-12
Back to the equation:
-(30m-12)
We get rid of parentheses
-30m+12
Back to the equation:
+(-30m+12)
We get rid of parentheses
2m/()-30m+12=0
We multiply all the terms by the denominator
2m-30m*()+12*()=0
We add all the numbers together, and all the variables
2m-30m*()=0

See similar equations:

| r(4.6)r=8.1 | | 8+c/5=11 | | -2q–1=-4–5q | | -2y+5=-(3y-3) | | c-96=6c-21 | | 5x+15=-x-30 | | (5x+3)=(2x-3) | | 9x+4x+3=5x+3+7x | | 3x-5=12x-23 | | s-602=-25s-4 | | 0.1=p/5 | | 9(2x+3)+2(9x-5)=4(17-18x)-3(5-9x) | | 12.5+mm=7.6 | | 5x^2-26x-18=0 | | 3f-7=10f | | -7x+75=x+219 | | 12.6x-2.1x=189 | | 2x²+16x+14-54=0 | | 8x-17=85 | | x2=16 | | 2x²+16x+14=54 | | -6(x+4)+2x+5=7x+6 | | -6=k=-9 | | u=-10+6u | | M=4m+15m-7 | | -14=4(v-5)-2v | | 3x(x-1)=2x-3+3x | | 8+45=a-53 | | 3x^2-7x+16=0 | | 7-2c=-3c | | -x+10=4x-15 | | 3a+10=65 |

Equations solver categories